Morphology and Stomach Content Analysis of Green Rough-Backed Pufferfish, Lagocephalus lunaris from Kuching, Sarawak - Mohamad, Samsur; Isa, Fadhilah (Borneo Journal of Resource Science and Technology, 2012)
A total of 101 individuals of green rough-backed pufferfish, Lagocephalus lunaris were collected at two sampling sites and were assessed for their morphological characteristics and diet by stomach content analysis. The physical characteristics were observed and body weight (BW), total length (TL), standard length (SL) and number of fins also had been measured. The results showed that the physical body measurement in all individuals were almost similar in their range of size (TL: 8.6 ± 0.3 cm; SL: 7.0 ± 0.2 cm; BW: 14.3 ± 1.5 g) and most individual had same distribution of spines at the dorsal part which extended to dorsal fin. The numbers of caudal, dorsal, pectoral and anal fin rays were counted, and ranged from 5 to 12, 7 to 11, 9 to 12 and 7 to 17, respectively. Analysis of the diet composition showed the fish is carnivores which prey on crabs, prawns, small fish and squids. The percent index of relative importance analysis was used to determine the important prey item of this species. From the results, crabs was identified as most important prey in Site 1 and Site 2, with value of (47.5, 55.6 %), and followed by prawns (36.3, 38.2 %), fish (5.6, 11.2 %), squids (0.7, 2.9 %) and bivalves (0.1, 1.7 %). To our knowledge, this is the first report to record the morphological characteristics and to determine stomach content of L. lunaris from Sarawak waters.